Analisis Nilai Moral Yang Terdapat Pada Novel Tembang Lara Karya Pipiet Senja - Achmad Yuhdi; Diza Afrillia (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
This study aims to examine the educational values in the novel entitled "Tembang Lara" by Pipiet Senja. Researchers hope that this research can be a source of teaching materials in learning moral values, namely love of God and all His creation, independence and responsibility, honesty / trust, respect and courtesy, benefactor, please help, and mutual assistance / cooperation, confident and hardworking, leadership and justice, humility, and tolerance, peace, and unity So that students can apply it to everyday life. The method used in this study is descriptive with a qualitative approach. The main source of data from this research is the content of the novel entitled "Tembang Lara" by Pipiet Senja. Data processing techniques use analytical descriptives, namely analyzing the data under study and then presenting the data that has been obtained by steps to collect data sources, read the novel "Tembang Lara" carefully, analyze the moral values in the novel, describe the moral values in the novel, and make conclusions about the moral values in the novel. In the novel "Tembang Lara" by Pipiet Senja found seven moral values, namely: 1) Love of God and all His creation, 2) Independence and Responsibility, 3) Honesty / trust, 4) Respect and Courtesy, 5) Help, and Mutual Cooperation / Cooperation, 6) Confident and Hardworking, 7) Leadership and Justice.